Human parainfluenza virus type 3 infections in a haemato-oncology unit: social distancing measures needed in outpatient clinics. (October 2021) - Anton-Vazquez, V.; Smith, M.; Mehra, V.; Avenoso, D.; Krishnamurthy, P.; Kulasekararaj, A.; Potter, V.; Pagliuca, A.; Zuckerman, M.
Summary: Background: Human parainfluenza virus type 3 (HPIV3) infections are associated with high mortality in immunocompromised settings, especially in bone marrow transplant recipients. Asymptomatic infection and lack of effective antiviral treatment makes HPIV3 prevention and treatment a real challenge. Aim: To retrospectively investigate the epidemiological characteristics, clinical characteristics and outcomes of 51 haematology patients with confirmed HPIV3 infections, detected between February and May 2019 in the haematology unit at King's College Hospital, London. Methods: Between February and May 2019, HPIV3 RNA was detected in combined nose and throat swab samples collected from 51 symptomatic haematology patients, 41 of whom attended the haematology outpatient unit. Clinical data were reviewed retrospectively and a timeline of patients' appointments drawn up to investigate transmission. Sequencing analysis was performed on 14 stored samples. Findings: Fifty-one patients were identified with HPIV3 infection. Mean age was 54 years (SD: 12; range: 19–72) and 60% (31/51) were male. There were 41 (80%) bone marrow transplant recipients, 24 had an allograft, and 17 an autograft. Thirty-day and 3-month mortality post HPIV3 was 6% and 14%, respectively. Lower respiratory tract infection and inpatient acquisition were associated with higher mortality (6/7 vs 1/7, P  = 0.010; and 5/7 vs 2/7, P  = 0.031). Onset of HPIV3 infection in patients within 6 days of attending the clinic was associated with the clusters identified in phylogenetic analysis (64% (9/14) vs 21% (8/37); odds ratio: 6.5 (confidence interval: 95% 1.7–25); P  = 0.006). Conclusion: Timelines suggested community transmission, but also possible transmission patterns within the outpatients and subsequent nosocomial transmission within the same ward. Early recognition of HPIV3 infection and the use of polymerase chain reaction and sequence analysis is fundamental in identifying respiratory virus outbreaks and person-to-person transmission. Careful planning of outpatient clinic attendance is required to minimize contact and prevent respiratory virus transmission in immunosuppressed patients.